The Impact of Dynamic Changes in Light Spectral Power Distribution on Cognitive Performance and Wellbeing. Issue 4 (1st October 2020) - Hartstein, Lauren E.; Tuzikas, Arunas; Karlicek, Robert F.
ABSTRACT: The spectral power distribution (SPD) of the indoor lighting environment can improve cognitive performance, as well as positively impact occupant wellbeing. Advances in solid-state lighting now allow the SPD of indoor light sources to change temporally to better match the dynamic quality of the natural environment. The present study sought to explore how rapid, dynamic changes in light SPD can impact cognitive performance and comfort compared to traditional, static indoor light fixtures. In this study, undergraduate students completed tasks measuring attention and processing speed, as well as questionnaires of sleepiness, emotion, and headache and eyestrain under traditional static lighting or a dynamic lighting condition consisting of fluctuations in light correlated color temperature (CCT) and constant illuminance. In Experiment 1, consistent, cyclical changes in CCT (4700–5300 K in a triangular wave pattern at a frequency of 0.03 Hz) were found to negatively impact participants' processing speed and reported ability to focus. However, these impairments were accompanied by a decrease in negative affect. In contrast, stochastic changes in CCT used in Experiment 2 (4700–5300K in semi-random changes at a frequency of 0.03, 0.07, or 0.10 Hz) produced no measured effects on participant task performance, alertness, mood, or comfort, suggesting that a degree of unpredictability in the frequency of changes in light CCT may be less disruptive to occupant performance and focus than regular, cyclical changes. The preliminary findings from this small-scale study highlight the need for further research into how changes in the lighting environment might be beneficial or detrimental to occupant performance and comfort.